2001
DOI: 10.1046/j.1360-0443.2001.961217253.x
|View full text |Cite
|
Sign up to set email alerts
|

The use of brief interventions adapted from motivational interviewing across behavioral domains: a systematic review

Abstract: To determine more effectively how well MI works in domains other than substance abuse and for whom it works best in all domains, researchers should study MI with risk behaviors other than substance abuse, while examining both interactions and the theoretical components of MI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
540
2
30

Year Published

2003
2003
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 802 publications
(583 citation statements)
references
References 24 publications
11
540
2
30
Order By: Relevance
“…Such repeated testing has been conducted on the use of motivational enhancement therapy for the treatment of nicotine, alcohol, and cocaine dependence (e.g. Dunn et al, 2001), and the use of cognitive-behavioral strategies for nicotine, alcohol and other drug dependences (Carroll, 1996). On the other hand, failure of initial studies with an arbitrarily chosen patient sample may lead to premature abandonment of a treatment with promise for abusers of another class of drugs.…”
Section: Inefficiency Of Behavioral Therapies Developmentmentioning
confidence: 99%
“…Such repeated testing has been conducted on the use of motivational enhancement therapy for the treatment of nicotine, alcohol, and cocaine dependence (e.g. Dunn et al, 2001), and the use of cognitive-behavioral strategies for nicotine, alcohol and other drug dependences (Carroll, 1996). On the other hand, failure of initial studies with an arbitrarily chosen patient sample may lead to premature abandonment of a treatment with promise for abusers of another class of drugs.…”
Section: Inefficiency Of Behavioral Therapies Developmentmentioning
confidence: 99%
“…The principles of MI include understanding the client's view, avoiding resistances by means of a non-confrontational approach and increasing clients' self-efficacy and the perceived discrepancy between their behavior and their current and long-term goals. Over the years this model of intervention has been shown to be effective in enhancing motivation towards change in several health-related behaviors [8]. Furthermore, some authors have stressed the importance of capitalizing on a teachable moment or window of opportunity [3], which provides good reason to conduct interventions in medical settings such as emergency rooms after a consultation related to substance-use.…”
Section: Introductionmentioning
confidence: 99%
“…Noonan and Moyers (1997) reviewed the 11 clinical trials of AMIs available at that time (9 with problem drinkers and 2 with drug abusers) and concluded that 9 of these studies supported the efficacy of AMIs for addictive behaviors. Dunn, DeRoo, and Rivara (2001) performed a systematic review of 29 randomized trials of brief interventions that claimed to use the principles and techniques of motivational interviewing (or what we have called AMIs) to change behavior in four areas: (a) substance abuse, (b) smoking, (c) HIV-risk reduction, and (d) diet and exercise. Data on methodological features were tabled, as were calculations of effect sizes and their 95% confidence intervals, although the authors chose not to combine or compare data meta-analytically.…”
mentioning
confidence: 99%